2021
DOI: 10.1080/19460171.2021.1879660
|View full text |Cite
|
Sign up to set email alerts
|

Assembling research integrity: negotiating a policy object in scientific governance

Abstract: In recent years research integrity has received increased attention from scientific governance. Many countries have opened up funding streams for research on (mis)conduct, and anumber of international policy efforts have emerged around the topic. In this paper we frame research integrity as a 'policy object' and reflect upon how this object is being assembled within one particular context, that of Denmark. Using material from an interview study with actors within Danish research, we outline how policy for rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…However, other research integrity researchers also already emphasize that there needs to be a shift in focus from individual researcher responsibilities to aspects of the 'system' (Bonn & Pinxten, 2019;Bruton et al, 2020;Sørensen et al, 2021). In addition, what is currently understood under research integrity seems to depend already on whom you ask (Davies, 2019;Davies & Lindvig, 2021). I would suggest that our goal in connection with funding should be to find out what the real problems on doing good and valuable science are -and ultimately, what issues funders and other science policy makers should address to improve the situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other research integrity researchers also already emphasize that there needs to be a shift in focus from individual researcher responsibilities to aspects of the 'system' (Bonn & Pinxten, 2019;Bruton et al, 2020;Sørensen et al, 2021). In addition, what is currently understood under research integrity seems to depend already on whom you ask (Davies, 2019;Davies & Lindvig, 2021). I would suggest that our goal in connection with funding should be to find out what the real problems on doing good and valuable science are -and ultimately, what issues funders and other science policy makers should address to improve the situation.…”
Section: Discussionmentioning
confidence: 99%
“…However, other research integrity researchers also already emphasize that there needs to be a shift in focus from individual researcher responsibilities to aspects of the ‘system’ (Bonn & Pinxten, 2019; Bruton et al, 2020; Sørensen et al, 2021). In addition, what is currently understood under research integrity seems to depend already on whom you ask (Davies, 2019; Davies & Lindvig, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This captures how the respective governments understand the norms they expect the research sector to live by. Thirdly, following Davies and Lindvig (2021), the responsibilities attributed by the law, along with their corresponding recipients. This allows for a discussion of the nature of the regulation of research integrity and ethics in the three countries, i.e., the extent to which researchers are expected to regulate themselves (laissez faire), criminalization, and metaregulation.…”
Section: Methodology and Analysismentioning
confidence: 99%
“…A similar issue has emerged in Denmark. Davies and Lindvig (2021) have shown that the interpretation of the Danish code of Conduct, which is formalized by the Danish law and forms the backbone of that system, varies from context to context and thus does not necessarily give clear guidance in practice.…”
Section: Trade-offs and Limitationsmentioning
confidence: 99%
“…Research integrity is a dynamic area recognized as vitally important by multiple stakeholders, including governments, funding institutions and the global scientific community 1,2 . Recently, the topic has been increasingly under the spotlight because of the necessity of creating appropriate scientific governance and other efforts to formalize and institutionalize good science 3 . According to Armond et al, academic interest in research integrity surged in the last decade for reasons such as the evolving nature of research environments due to the introduction of new technologies, the pressure to publish, competition for funding, diversification in collaboration, and the rise in publicized cases of misconduct 4 .…”
mentioning
confidence: 99%